Communicative Approach in Teaching English As A Foreign Language - Bertaria Sohnata Hutauruk (Bandar Lampung University (UBL), 2013)
This study concerns on the teacher’s communicative approach in teaching English as a foreign language which was taken at English department in FKIP UHN Pematangsiantar. The problem of the research is what are teacher’s techniques used in teaching English as a foreign language? The writer used some theories related to the Techniques of Teaching English and communicative approach theory as the following: Allen (1965), Abbot (1981), Billow (1961), Byrne (1976), Lado (1979), Larsen (2000), This research is a qualitative research which based on the reality teaching and learning process in English class at FKIP UHN Pematangsiantar. The methodology covers the research design, instrument, technique of collecting data, data analysis and interpretation. The teacher‘s communicative approach are mostly use direct method, cooperative learning and audio lingual method. To be communicative in teaching English, the teacher also recommended use communicative competence and some variation technique in teaching and learning process. The teacher should try himself best in teaching English as a foreign language so the students understand more easily the materials. The writer gives suggestion to deal with the teacher’s techniques in teaching English in the classroom to make them more active in interaction. The good teaching will be done using communicative approach, techniques, preparing lesson before starting the lesson, knowing the background of the students and giving motivation to communication accuracy and fluently directly